Risk factors for early childhood caries in patients with cleft lip and palate: a descriptive study - Bella, Priskilla Kristiana; Setiawan, Asty Samiaty; Putri, Fidya Meditia (Universitas Padjadjaran, 2024)
Introduction: Cleft lip and/or palate is a common congenital defect. Children with this condition often experience abnormalities in the anatomical and morphological structures of the oral cavity, which contribute to poor oral hygiene and a lack of interest in maintaining dental care. Early Childhood Caries (ECC) is a prevalent dental health problem in patients with cleft lip and/or palate and is affected by factors such as sugary food consumption, oral hygiene habits, frequency and use of milk bottles, and parental socioeconomic status. This study aims to identify the risk factors for ECC in children with cleft lip and/or palate. Methods: This study employed descriptive research methods, using interviews with ECC risk factor questionnaires and purposive sampling based on Taro Yamane's formula, resulting in a sample of 91 parents of children diagnosed with cleft lip and/or palate. The questionnaires used in this research had undergone validity and reliability testing. The results were analyzed using frequency distribution. Results: The results of this research showed that most respondents had education level equivalent to junior high school or high school (51.65%). The respondents' average income was below 1.5 million as follows, accounting 47.25% of the sample. All respondents (100%) demonstrated good knowledge of maintaining their children's oral hygiene. However, the majority of respondents provided sweet foods (51.65%) and sweet drinks (43.65%) to their children 1-3 times per day. Additionally, 49.45% of respondents reported giving milk to their children before sleep, and 45,05% indicated that their children sometimes fell asleep eating without brushing teeth. Conclusion: The risk factors for ECC in patients with cleft lip and/or palate include parental education and income, children's habit of sleeping after eating without brushing their teeth, frequency of sugary foods consumption, frequency of formula milk consumption, and the practice of giving milk to children before bedtime.